Religious and economic soft power in Ghana-Turkey relations - Haynes, Jeffrey (MDPI, 2022)
Turkey’s government seeks to apply both “religious soft power” and “economic soft power” to increase its influence in Ghana. Turkey’s religious soft power relationship with Ghana is exemplified by Turkey’s paying for construction of a new national mosque in the African country, at a cost of USD 10 million. Turkey’s economic soft power relationship with Ghana is exemplified by both considerable recent investments and in fast-growing bilateral trade. The overall aim of the government of Turkey is to increase the country’s influence in Ghana, part of a wider initiative to expand its regional influence in Africa. Ghana is important to Turkey as it is regarded as a strategically important African country, one of the region’s few democracies and an economic success. The paper assesses Turkey’s various forms of influence in Ghana and considers what Turkey hopes to achieve in foreign policy terms. The paper is in four sections. The first examines religious soft power and Turkey–Ghana relations, noting that recently they have become closer and more cordial, involving both religious and non-religious aspects. The second section examines Muslims’ traditionally marginal political position in Ghana and explains that over time Muslims have become more politically assertive, open to external religious influences, including from Turkey, a country well known to use religious soft power to try to expand its foreign policy influence. The third section assesses recent Ghana-Turkey relations, including the expansion of Turkey’s economic soft power, with three examples: the national mosque, encouraging Islamic education, and mutual desire to quell the activities of what the government of Turkey refers to as the “Fethullah Terrorist Organisation”. The section also considers the role of Turkey’s economic soft power in increasing the country’s presence in Ghana. The concluding section argues that the government of Turkey uses several techniques to increase its influence in Ghana, including both religious soft power and economic soft power. The government of Ghana broadly welcomes Turkey’s influence from both religious and economic perspectives: from a religious point of view, Turkey’s Sunni orthodoxy is seen as very unlikely to stimulate radicalization among Ghana’s Muslims, while Turkey’s economic presence is welcomed as an important means to help further build Ghana’s economy.